PENERAPAN PERJANJIAN TERTULIS DALAM KAITAN PERLINDUNGAN HUKUM TERHADAP PARA PIHAK DALAM USAHA WARALABA ONLINE - Junaidi Abdillah (Justici, 2022)
ABSTRACT In a franchise business, in general, it requires an agreement where the existing agreement is a standard agreement that has been made in advance by the franchisor. The franchisee when agreeing to the offered franchise business must be subject to the existing agreement. This should also apply to franchise businesses offered online. A written agreement is one aspect of legal protection to the parties from harming other parties, this is because the agreement can be a strong legal basis for enforcing legal protection for the parties involved in the franchise system, if one party violates the contents of the agreement, then the other party may sue the infringing party in accordance with applicable law